Hepatic Autonomic Nervous System and Neurotrophic Factors Regulate the Pathogenesis and Progression of Non-alcoholic Fatty Liver Disease - Amir, Muhammad; Yu, Michael; He, Peijian; Srinivasan, Shanthi (Frontiers in Medicine, 2020)
Non-alcoholic fatty liver disease represents a continuum of excessive hepatic steatosis, inflammation and fibrosis. It is a growing epidemic in the USA and worldwide. Progression of non-alcoholic fatty liver disease can lead to morbidity and mortality due to complications such as cirrhosis or hepatocellular carcinoma. Pathogenesis of non-alcoholic fatty liver disease is centered around increased hepatic lipogenesis and decreased hepatic lipolysis in the setting of hepatic and systemic insulin resistance. Adipose tissue and hepatic inflammation can further perpetuate the severity of illness. Currently there are no approved therapies for non-alcoholic fatty liver disease. Most of the drugs being explored for non-alcoholic fatty liver disease focus on classical pathogenic pathways surrounding fat accumulation. Studies have demonstrated that the autonomous nervous system innervating the liver plays crucial role in regulation of hepatic lipid homeostasis, inflammation and fibrosis. Additionally, there is growing evidence that neurotrophic factors can modulate all stages of non-alcoholic fatty liver disease. Both the autonomous nervous system and neurotrophic factors can be altered in patients and murine models of non-alcoholic fatty liver disease. In this review we focus on the pathophysiological role of the autonomous nervous system and neurotrophic factor signaling pathways that could be potential targets for novel therapeutic approaches to treat non-alcoholic fatty liver disease.